2020
DOI: 10.1186/s13063-020-4080-2
|View full text |Cite
|
Sign up to set email alerts
|

Aim2Be mHealth intervention for children with overweight and obesity: study protocol for a randomized controlled trial

Abstract: Background: The prevalence of overweight and obesity remains high in Canada, and the current standard for the treatment of childhood obesity is in-person, family-based, multidisciplinary interventions that target lifestyle behaviors (e.g., diet, physical activity, and sedentary behaviors). These programs are costly to operate, have limited success, and report recruitment and retention challenges. With recent advances in technology, mobile health or mHealth has been presented as a viable alternative to in-perso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 52 publications
1
32
0
1
Order By: Relevance
“…While Aim2Be can also be accessed via a home computer >95% of the participants downloaded the app on their phones. Briefly, the Aim2Be app is a gamified health behavior modification program that supports adopting healthy behaviors such as improving dietary quality, increasing physical activity, reducing screen time, and improving sleep (see theoretical description eslewhere ( Mâsse et al, 2020 ). In addition, Aim2Be integrates a living green focus (i.e., addresses how health behaviors impact the environment) as well as emphasizes healthy body image and self-esteem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Aim2Be can also be accessed via a home computer >95% of the participants downloaded the app on their phones. Briefly, the Aim2Be app is a gamified health behavior modification program that supports adopting healthy behaviors such as improving dietary quality, increasing physical activity, reducing screen time, and improving sleep (see theoretical description eslewhere ( Mâsse et al, 2020 ). In addition, Aim2Be integrates a living green focus (i.e., addresses how health behaviors impact the environment) as well as emphasizes healthy body image and self-esteem.…”
Section: Methodsmentioning
confidence: 99%
“…This paper aimed to address these aforementioned research gaps, by evaluating version (v1) of the Aim2Be app – an mHealth gamified lifestyle behavior modification app for teens and their parents with the goal of improving children’s dietary quality (i.e. increasing fruit and vegetable intake, reducing sugar-sweetened beverage intake), increasing physical activity, reducing screen time, and meeting sleep recommendations ( Mâsse et al, 2020 ). Specifically, this paper: 1) examined teens engagement with the main features of Aim2Be; 2) investigated whether teens’ profiles of engagement differed by socio-demographic characteristics and parental engagement; and 3) assessed whether engagement profiles were associated with change in the targeted mediators (knowledge, self-efficacy, and intrinsic motivation) and/or health behaviors primarily targeted by the app.…”
Section: Introductionmentioning
confidence: 99%
“…To date, four research groups took the initiative to develop multidisciplinary serious games including different game modules that can be used to promote healthy behaviors in children with obesity. Three of them were recently published ( Espinosa-Curiel et al, 2020 ; Mack et al, 2020 ; Ruggiero et al, 2020 ), while one is still in progress ( Mâsse et al, 2020 ). The overall content (i.e., available online) and outcome goals were to provide knowledge, enhance motivation, and encourage behavior change related to healthy eating, PA, and stress coping.…”
Section: Multidisciplinary Serious Gamementioning
confidence: 99%
“…In [35], it is shown that 76% of overweight pediatric patients abandon treatment after 6 months, alleging a lack of time to attend checkups and a lack of tools to support their treatment from home. This problem is highlighted by the World Health Organization (WHO), which suggests that the development of telemedicine and mHealth, in that sense, should include parents or caregivers of children as agents of change during the treatment of patients [1,30]; only in this way could be overcome the barriers of face-to-face visits, long distances and insufficient resources [18,27].…”
Section: Mhealth For Obesity In Pediatric Patientsmentioning
confidence: 99%
“…The family member, following the indications of the specialist (via Videoconferences) or the application (which uses the home protocol of the Centers for Disease Control and Prevention [27]), enters the following data in the application: weight in kilograms or pounds, height in meters, waist in centimeters, and other data such as age, gender, and region. Then, on the mobile device, the calculation of the Body Mass Index (BMI) is obtained from the formula: weight/(height x height) [3], which, together with the waist circumference, are the indicators used to identify the nutritional status of the patient.…”
Section: A Capturementioning
confidence: 99%